Association Between Dietary Intake of Polychlorinated Biphenyls and the Incidence of Hypertension in a Spanish Cohort: The Seguimiento Universidad de Navarra Project. Issue 4 (April 2015) - Donat-Vargas, Carolina; Gea, Alfredo; Sayon-Orea, Carmen; de la Fuente-Arrillaga, Carmen; Martinez-Gonzalez, Miguel Angel; Bes-Rastrollo, Maira
Abstract : Polychlorinated biphenyls are persistent organic pollutants that are consumed because of their bioaccumulation through the food chain. Evidence from different sources suggests a positive association between polychlorinated biphenyls exposure and the incidence of hypertension. However, no previous prospective study has investigated this potential relationship in adults. We prospectively assessed the association between dietary intake of polychlorinated biphenyls and the incidence of hypertension in a large cohort. The Seguimiento Universidad de Navarra project is a Spanish cohort of university graduates, most of them health professionals. We included 14521 participants, initially free of hypertension, who were followed-up for a median of 8.3 years. Dietary intake of polychlorinated biphenyls was assessed at baseline through a previously validated 136-item semiquantitative food frequency questionnaire. The published concentration levels of polychlorinated biphenyls measured in samples of food consumed in Spain were used to estimate dietary intake. Multivariable Cox regression models were fitted to estimate hazard ratios and 95% confidence interval for incident hypertension. During follow-up, 1497 incident cases of medically diagnosed hypertension were identified. After adjusting for total energy intake and for potential confounders, participants in the fifth quintile of total polychlorinated biphenyls intake were at higher risk of developing hypertension (adjusted hazard ratio, 1.43 [95% confidence interval, 1.09–1.88; P for trend 0.017]) compared with those in the first quintile. In this Mediterranean cohort, dietary intake of polychlorinated biphenyls, estimated using a food frequency questionnaire, was associated with a higher risk of developing hypertension during follow-up. Nevertheless, further longitudinal studies are needed to confirm our results. Abstract : Supplemental Digital Content is available in the text.